Exploring Digital Skills of Professional Accountants: Literature review from 2021-2025 - Ana NOVAK (Communications of International Proceedings, 2025)
Although information technology has long been used in accounting, the integration of advanced digital technologies is increasingly transforming traditional accounting tasks. Therefore, professional accountants need to possess a range of skills, including appropriate digital skills, to perform effectively in the digital age. This paper aims to synthesise the current state of knowledge regarding the digital skills expected of professional accountants by analysing findings from recent academic studies. A literature review was conducted using the Web of Science Core Collection database, focusing on studies published in the period from 2021 to 2025 and covering various world regions. The review explores the categorisation of digital skills as well as related digital technologies, highlighting the key digital skills expected of professional accountants in contemporary accounting practice. The findings highlight a broad range of digital skills that are essential for professional accountants to acquire and apply in their work. According to the results, professional accountants have developed basic digital skills. However, the increasing adoption of advanced and emerging technologies in accounting practice requires the continuous acquisition of new digital knowledge and the further development of digital skills. The findings of this paper provide insights into the current state of knowledge regarding the digital skills expected of professional accountants, which can be useful to a wide range of stakeholders, particularly accounting educators, by offering insights that can support the alignment of accounting curricula with labour market expectations of professional accountants regarding digital skills in the contemporary digital environment.
Keywords: digital skills; digital technology; professional accountants; accounting profession